(untitled) (Jurnal Teknologi (Sciences & Engineering), 2014)
Liquefied Natural Gas (LNG) tanker often travels through shallow waters with visible banks to load and unload its hazardous cargo. Manoeuvring of vessel in shallow water is relatively difficult and always exposed to higher risk of grounding and collision compared to deep water due to effect of ship-bank interaction. This research work examines ship-bank interaction effects of a LNG tanker in shallow water. CFD analysis is performed to investigate the hull hydrodynamic forces/moments and ship-bank interaction forces/moments which are further validate by captive model tests.